Vegetable Juices – The Most Awaited Therapeutics for a Highly Prized Target, PTP 1β - Sweeya, Pisupati SR; Gandham, A Priyadarshini; Rodda, Raghuveer; Chidrawar, Vijay R; Rao, V. Uma Maheswara (Asian Journal of Pharmaceutical Research and Development, 2013)
Constitution of the World Health Organization (WHO) defines health as, “a state of complete physical, mental and social well-being and not merely the absence of disease or infirmity.” According to views like this, we shouldn’t think in terms of health and disease alone, rather in terms of ‘health’, ‘disease’ and ‘normality’. Vegetables have been identified as an economical natural source of potent antioxidants and considered important in the maintenance of health and prevention of several diseases. Although, they were well reported for their beneficiary effects in diabetics, their mechanism-based therapeutics was not completely understood. In this study, an attempt was made to present the potential of these vegetable juices in becoming functional foods and also to discover the mechanism behind their preventive and therapeutic properties against diabetes and associated complications. Several scientific reports proved vegetables to be very good inhibitors of the most desired drug target, PTP 1β, both in-vitro and in-vivo; research finds vegetables’ juices helping not only to improve the diseased state but also in promoting good ‘health’ rather than just ‘normality’ thus serving as a functional food.